Integration of Perforator Vessels in CAD/CAM Free Fibula Graft Planning: A Clinical Feasibility Study. - Goetze, Elisabeth; Kaemmerer, Peer W.; Al-Nawas, Bilal; Moergel, Maximilian (Journal of Maxillofacial and Oral Surgery, 2020)
Introduction: Commercial CAD/CAM planning of free osteocutaneous microvascular fibula flap does not support integration of soft tissue structures including perforator vessel anatomy. Therefore, in a clinical trial, a method for such a combined hard- and soft tissue 3D-fibula planning was assessed. Materials and Methods: In a clinical study on 24 patients needing reconstruction with osteocutaneous fibula graft, skin perforators of the respective leg were detected via Doppler sonography and documented on a measurement device. Each of the perforators' localization was transferred to a CAD/CAM planning software and included in each planning step as well as in the surgical cutting guide. A comparison between sonography and clinical localization, damage to perforator vessels during surgery as well as a subjective evaluation of feasibility and usefulness of the procedure was carried out. Results: In total, 19 skin paddles were placed orally, 2 extraorally and 3 at both sites at once. Survival rate was 92% (22/24). In addition, 3 skin paddles were lost complete and 2 partially. Anatomical sites of perforator vessels were never < 1 cm from planned positions and not damaged at all (n = 75). Planning was judged useful for skin paddle design and positioning of osteotomies. In accordance, surgical guides were always implemented successfully without the need of changing planned procedures during surgery. Conclusion: Integration of skin perforators into 3D planning of microvascular fibular graft is feasible and may even decrease involuntary dissection of perforator vessels. Even so, clinical studies for comparison are needed.
EVALuna2:484021